Nation Games History and Historiographical Imperatives in India - Zachariah, Benjamin 1972- (De Gruyter Oldenbourg, 2020)
This volume examines the tension between the "nation" idea as a necessary language of legitimacy with which to claim liberation, and its role in disciplining people and their identities in India, in the name of national liberation. It is an attempt to open up new lines of thinking, and ways of reading Indian history
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Aug 2020)
Keywords: Geschichte; Geschichte Indiens; Global history; Globalgeschichte; Historiographie; Historiography; History of India; National history; Nationalgeschichte; HISTORY / Modern / General; Unabhängigkeitsbewegung; Geschichtsbewusstsein; Nationalismus; Faschismus; Hinduismus; Europa; Indien